Analisis Kebijakan Kabupaten Kuningan Sebagai Kabupaten Konservasi (Evaluasi terhadap Perda 9/2014 Tentang RPJMD Kabupaten Kuningan) - Alif Muhammad Ikbal; Budi - Setiyono (Journal of Politic and Government Studies, 2020)
Kuningan District through the local regulations No. 9 of 2014 concerning The Regional Medium Term Development Plan (Rencana Pembangunan Jangka Menengah Daerah /RPJMD) 2014-2018 in the past 2006. Had been declarated as “Conservation District” which is the entire of Kuningan District development concepts was applying conservation principles and the fourth mission in RPJMD of Kuningan district in 2014- 2018 that is “Strengthen the preservation of natural resources and the environment within the framework of a conservation district by applying the principle of sustainable living.” This research has purposed to analysing conservation district policies at Kuningan District in the 2014-2018 period. The method was used in this research is qualitative methods are carried out through in-depths interviews with reserach infomants as primary data totaling 10 people from Bappeda Kuningan Regency, Kuningan Regency Environmental Service, academics, environmental NGO’s and community representatives around the conversation area in Kuningan District. In addition, this study uses secondary data analysis. The results of this research has indicated, there are several objective indicators in the mission of fourth point in the 2014-2018 RPJMD, namely: the increase in the percentage of regional unity green open space, the increase in the ratio of protected areas, making Kuningan District zero critical land and the formation of disaster resilient villages. Based on the analytical study that has been carried out, the Kuningan Regency Government has not met the target achievementsin several of these objective indicator points. Some of the obstacles faced by the Kuningan Regency Government in realizing its area as a conservation district are the lack of budget, the unavailability of a legal framework regarding a conservation district and the utilization of production land for community in Kuningan district is still not optimal